A structural biology perspective on NMDA receptor pharmacology and function. (August 2015) - Regan, Michael C; Romero-Hernandez, Annabel; Furukawa, Hiro
Highlights: The NMDA receptor is a membrane protein critical to mammalian learning and memory. Heterotetrameric NMDARs consist of three structured domains that regulate ion flux. Small molecule binding at different sites can dramatically affect channel activity. Recent structural work provides a framework for understanding NMDAR regulation. Abstract : N -methyld -aspartate receptors (NMDARs) belong to the large family of ionotropic glutamate receptors (iGluRs), which are critically involved in basic brain functions as well as multiple neurological diseases and disorders. The NMDARs are large heterotetrameric membrane protein complexes. The extensive extracellular domains recognize neurotransmitter ligands and allosteric compounds and translate the binding information to regulate activity of the transmembrane ion channel. Here, we review recent advances in the structural biology of NMDARs with a focus on pharmacology and function. Structural analysis of the isolated extracellular domains in combination with the intact heterotetrameric NMDAR structure provides important insights into how this sophisticated ligand-gated ion channel may function.